NEONATAL GASTROINTESTINAL MUCORMYCOSIS (GIMM), A MIND-BOGGLING PRESENTATION IN LMIC - Ashraf, Madiha; Sahrish, Fariha; Akram, Aysha; Ahmad, Alia; Arshad, Shehla; Irum, Saima (Infectious Diseases Journal of Pakistan, 2022)
Background: Gastrointestinal mucormycosis is a rare infection acquired by ingesting contaminated products. It primarily affects the stomach, followed by the colon and ileum. Premature and low birth weight neonates are explicitly susceptible. Contaminated nasogastric tubes, endotracheal tubes, wooden tongue depressors, the warm, humid environment of the Intensive Care Units, contaminated enteral feeds, and parenteral infusions are considered culprits in a hospital. The most important differential diagnosis of MM is necrotizing enterocolitis. The gold standard methods to diagnose MM are Histopathology, Culture & sensitivity, and molecular testing in high-risk patients. Material and Methods: It is a retrospective descriptive study conducted from January 2015 to January 2016 at Children’s Hospital Lahore. All neonates who presented with intolerance to feed, abdominal distension, failure to pass meconium, respiratory distress, and pneumoperitoneum needing abdominal surgery were included. Per-operatively specimens were obtained like gangrenous gut resections or serial six biopsies in case of suspected Hirschsprung disease. An end-to-end anastomosis or an ileostomy stoma was performed depending on the patient’s clinical condition. Results: Of the 121 neonates, enrolled preterm were (55.3%) and low birth-weight males were (67.7%). They presented with abdominal distension (100%), and had (51.2%) pneumoperitoneum. Most neonates were suspected of having necrotizing enterocolitis (NEC) and showed dilated bowel loops on the x-ray abdomen (93.3%).After surgeries, two complications, short gut syndrome (8.2%) and intolerance to feeding (13.2%), were seen in these patients. Three pre-term neonates suspected clinically as NEC were found to have GIMM. The histopathology report showed numerous broad aseptate fungal hyphae with extensive necrotizing inflammation and infarction of the bowel wall. Conclusion: . Keywords: Mucormycosis, Necrotizing enterocolitis, Neonates